Applied Online Bubble Size Distribution Measurement in a Pilot Flotation Cell Based on Image Analysis - Leiva, C. A.; Borjas, Jose; Acuña, Claudio; Luukkanen, Saija (European Journal of Applied Sciences, 2023)
The distribution of bubble size in the pulp is a parameter directly related to the flotation kinetics, but its measurement is complex to determine due to the presence of particles and cluster of bubbles. The existing equipment for the measurement of bubble size (McGill and UCT), which operate manually and batch, requires specialized operators in image analysis. On the other hand, the McGill technique has not been directly validated with bubble swarms and only 10% of the sampled bubbles are analyzed. These aspects have limited the technology transfer and sustainability in the measurement of bubble size. To solve the problems presented, a device based on the McGill technique was designed and implemented. Furthermore, algorithms were implemented to increase the statistical significance of the measurement of bubbles per image. The validation consisted of a comparison of the degree of detection using the software manually and automatically (undetected remaining bubbles). As a result, it is possible to predict the bubble size distributions with an error of less than 5% and derivations close to 0.1 [mm] in the determination of D32, using an average of 100 images. In conclusion, the new device and algorithms improve the accuracy of BSD measurements, helping to optimize the process, predict, control flotation kinetics, and be used as a troubleshooting tool. The new device and algorithms improve the accuracy of BSD measurements, helping to optimize the process, predict, control flotation kinetics, and be used as a troubleshooting tool.